Mewujudkan Perilaku Hidup Bersih Dan Sehat Dengan Cuci Tangan, Pola Makan Sehat, Dan Pengelolaan Sampah - Willy Arya Wicaksana; Gita Wulandari; Dhian Satria Yudha Kartika (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Community service activities in the context of KKNT SDG’s which have been carried out in flat B block, Gunung Anyar Village, RW 4, RT 4, Surabaya, use an approach in the form of educational outreach to the children of flat residents starting from pre-school to grade 6 of elementary school. The aim of this service is to provide understanding and awareness from an early age about the importance of a clean and healthy lifestyle to minimize disease and malnutrition. The materials practiced through this activity are washing hands with soap and clean water, eating healthy food, and throwing rubbish in the right place. The results of the socialization have the impact of increasing the enthusiasm and understanding of the children who have participated. Therefore, cooperation between the government and the community is needed in providing education and facilities to implement a clean and healthy lifestyle from an early age.